Apparent and occult infections of medical staff in a COVID-19 designated hospital - Guozhen Li; Caiying Hu; Qiong He; Jing Liu; Nian Xiong; Haizhou Wang (Elsevier, 2020)
Since the outbreak of novel coronavirus (SARS-CoV-2)-infected pneumonia (COVID-19), numerous medical staff are fighting on the frontline. However, the possibility of occult infection in medical staff is ignored in many recent studies. Herein, we collected data in a COVID-19 designated hospital from January 22, 2020 to March 10, 2020. A total of 33 medical staff had at least one nucleic acid test of throat swab, immunoglobulin G (IgG) or IgM serum antibody test, and chest computed tomography (CT), were enrolled. Finally, we identified 25 cases (75.8%) were isolated for hospitalized treatment after positive virus detection. In addition, 4 cases who were all negative for nucleic acid test detection with no clinical symptoms, and none of their chest CT were abnormal. However, the results of serum IgG or IgM antibody test in these 4 cases were positive, suggesting the presence of occult infection. In conclusion, data from our single center indicated that SARS-CoV-2 had a high medical infection rate (29/33 = 87.9%) and might have a potential risk of occult infection.